Harmonization and integration of water saving options in Cyprus - Chimonidou D.; Polycarpou P.; Vassiliou L.; Papadopoulos I. (Harmonization and integration of water saving options. Convention and promotion of water saving policies and guidelines, 2007)
For Cyprus, water is the most important resource and a prerequisite for progress. Its scarcity has acted as a limiting constraint for the development of agriculture and for other economic activities such as tourism. Irrigated land, accounts 35.100 hectares or 16,2% of the total area enumerated and 57% of the annual amount of water for irrigation purposes is provided mainly from Government Irrigation Schemes. In the Government schemes the sources of water used are surface water, groundwater and reclaimed water. As a rule, the water demand in the non- Governments chemes is satisfied by groundwater. The scarcity of water together with the high cost associated with collecting and using the limited surface rain water for irrigation, has become real constraints for our irrigated agriculture. Because of this, particular emphasis is placed on the water use efficiency and modern irrigation technology. Modern irrigation systems have been used in Cyprus agriculture for the last 40 years. It is estimated that currently over 95% of the total irrigated land of the country is being served by modern irrigation methods. Recently, particular emphasis was laid on protected cultivation and more specific on cultivation of vegetables and flowers on substrates and soilless cultures (closed systems and open with minimum drainage). At the Agricultural Research Institute, the use of local materials i.e. perlite, mixtures of perlite with pomace, almond shells, pine bark etc. have been tried successfully. In this paper, results of the application of modern techniques, hydroponic cultures, recirculation of irrigation water and nutrient solution in closed systems and control of the climatic conditions in the greenhouse are discussed. In making the supply meet the demand the Government policy has encouraged and adopted management measures as water rationing, increase of public awareness for water conservation measures and water pricing for improvements in the water use efficiencies. The main measures, as well as the new Government water policies, are discussed in this paper.
5. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2006/05/03-07, Malta (Malta)